How does housing tenure mix affect residents' mental health through a social environment lens? An empirical examination from Guangzhou (China) - Zhang, Tianyao; Li, Xin; Liu, Jiahui (Frontiers in Public Health, 2023)
This study demonstrates the mechanisms of housing tenure mix affecting residents’ mental health via intervening community social environment within public housing practices in urban China. Using a purposive sampling data of six representative public housing estates, we used structural equation models to examine total, direct, and indirect effects of housing mix status on mental health, highlighting the intermediatory roles of social environment variables. On the whole, we find no significant impact of housing tenure mix on mental health; however, housing tenure mix thwarted mental health in a direct way but contributed to it through the mediation of social participation. Regarding the neighbourhood effects, we unfold the behavioural, psychological, and socially interactional mechanisms for affecting mental health, by highlighting the direct health implications of social capital, and the mediation of sense of community and social control between social capital and mental health. Finally, we suggest to consider social effects on health grounds into mixed housing strategies in future.